Dimensiuni sociale ale succesului şcolar: rolul şcolii şi comunităţii în performanţa şcolară a elevilor - Dămean, Diana; Roth, Maria (Calitatea Vieții, 2009)
The research is based on the outcome of a pilot survey for The Social Diagnosis of School Performance using the social scale of school success and designing an evidence-based intervention methods project that aims to identify and evaluate efficient methods for improving the social aspects of school success. The project is mainly focused on validating an instrument designed at the Chapel Hill University (USA), called the School Success Profile in Romania. The article focuses on the associations between neighbourhood and school safety, and students’ attendance, trouble avoidance in school and grades. The instrument is based on an ecological perspective and contributes to the identification of adolescents most likely to encounter school-risk situations. We have chosen this research design in order to prove that the above mentioned social factors need to be included in the strategy for improving the educational management. Educational innovation may begin, in our opinion, with a situational analysis of these variables and may be continued with the appropriate interventions. A real preoccupation for students’ school success must acknowledge the variables highlighted in this study, which can be altered by the appropriate intervention programs.